Mobile applications for the health and care of elderly - Diane Nogueira Paranhos Amorim; Luísa Veríssimo Pereira Sampaio; Gustavo de Azevedo Carvalho; Karla Helena Coelho Vilaça (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
The increasing use of smartphones, coupled with the aging of the population, has brought to the market several applications aimed at the elderly public. Faced with this reality, the objective of the study presented on this article was to describe the applications directed to the health and care of the elderly. We searched for applications on smartphones with Android and iOS operating systems. The descriptors used in the search were: 'idoso', 'saúde do idoso', 'envelhecimento', 'elderly' and 'health of the elderly'. 25 applications covering three themes were found: elderly health, elderly care, and health and care information about the elderly. The applications aim the practice of physical exercise, the prevention or detection of falls, the cognitive stimulation, the search for professionals or services, the assistance of elderly care and the dissemination of information on health and on diseases and treatments. Applications for smartphones can make a great contribution to health and the improvement of elderly care, being an instrument for monitoring, information and promotion of healthy habits.